(3GdbGfhf GdUZjQ aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdQFjS GdaGVd GdQFjS GdLdjd CHh Ydi Hf SjfG QMeg Gddg (B: (3GdMeO ddg GdPi LYd GdMeO RjfI cd bhd , adjS jMSf bhd hEf HQY s
(3BNQgG (B:s
(3hbO jYLR egQI GdCWHGA Yf gPG GdMei , acja ef djS HWHjH? hGdhLg Cf jdJLF GdCeQ ajg Edi GdWHjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B178 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(868) s
Keywords: (3GdWHs